1953
DOI: 10.1021/ja01105a022
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted Lactamides

Abstract: May 5, l9d.3 N-SUBSTITUTED LACTAMIDES 2097 the catalyst and solvent left a red sirup which readily crystallized to a yellow solid when heated with 100 ml. of water and 20 ml. of concentrated ammonium hydroxide. Most of the color could be removed by slurrying with cold ethyl acetate. Three experiments gave 25.2, 23.2 and 26.5 g. of crude product (melting above 146') suitable for the next step. A sample recrystallized from ethanol melted a t 154-155" uncor.Anal. Calcd. for C1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It seems that, from the above results, PLA was directly aminolyzed by 2a over [N 4444 ][Lac]. Considering that PLA can be hydrolyzed to LA ( 11 ) and LA can react with 2a to form 3a ( 16 ) under the catalysis of suitable catalysts, [N 4444 ][Lac] was examined for catalyzing hydrolysis of PLA and reaction of LA with 2a , respectively. It was indicated that [N 4444 ][Lac] was effective for both reactions, producing corresponding LA and 3a in high yields ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that, from the above results, PLA was directly aminolyzed by 2a over [N 4444 ][Lac]. Considering that PLA can be hydrolyzed to LA ( 11 ) and LA can react with 2a to form 3a ( 16 ) under the catalysis of suitable catalysts, [N 4444 ][Lac] was examined for catalyzing hydrolysis of PLA and reaction of LA with 2a , respectively. It was indicated that [N 4444 ][Lac] was effective for both reactions, producing corresponding LA and 3a in high yields ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…N-substituted lactamides are a kind of valuable chemicals widely applied in chemical industries, which are generally produced via dehydrative coupling reactions of LA with amines (16)(17)(18)(19), suffering from inherent disadvantages such as low efficiency due to the equilibrium reaction and waste production caused by removal of acid or base catalysts. From the viewpoint of sustainable development, green and efficient approach is highly required.…”
Section: Introductionmentioning
confidence: 99%
“…[6] A summary of experimental conditions is given in Table 1. The first application of DKR strategy was the asymmetric esterification of racemic ibuprofen, flurbiprofen and fenoprofen [7] ( Figure 2) with all lactamides, performed in the presence of 1.0 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…The chiral auxiliaries were readily synthesized according to the literature procedures by simple aminolysis of (S)-ethyl lactate 7 or (S)-lactic acid 8 with a slight excess of dibenzylamine, dimethylamine and pyrrolidine, and purified through distillation or recrystallization. Alternatively, the synthesis of amide (S)-1c was performed under Weinreb amidation conditions, by stirring (S)-ethyl lactate with pyrrolidine, in the presence of equimolar amount of trimethylaluminium; the function of the catalyst is to generate dimethylaluminium amides that react in a relatively short time with ethyl lactate.…”
Section: Figurementioning
confidence: 99%